Direct measurement of the coupled spatiotemporal coherence of parametric down-conversion under negative group-velocity dispersion - Cutipa Giménez, Paula; Spasibko, Kirill Yu; Chekhova, Maria (Optics Letters, 2020)
We present a direct measurement of the spatiotemporal coherence of parametric down-conversion in the range of negative group-velocity dispersion. In this case, the frequency-angular spectra are ring-shaped, and temporal coherence is coupled to spatial coherence. Correspondingly, the lack of coherence due to spatial displacement can be compensated for with the introduction of time delay. We show a simple technique, based on a modified Mach-Zehnder interferometer, which allows us to measure time coherence and near-field space coherence simultaneously, with complete control over both variables. This technique is also suitable for the measurement of second-order coherence, where the main applications are related to two-photon spectroscopy.
CRIS-Team Scopus Importer:2020-07-24